Siderophore‐Assisted Dissolution of Iron(III) Hydroxide Oxides from Iron‐Rich Fossil Matrices. Issue 8 (13th August 2020) - da Costa, Justin; Cohen, David R.; Magalhães, M. Clara F.; Hibbert, D. Brynn; Archer, Michael; Myers, Troy J.; Hand, Suzanne J.
Abstract: Current paleontological techniques to separate vertebrate fossils from encasing iron‐rich cements by chemical means are limited by the low solubility of common iron(III) hydroxide oxides such as hematite and goethite. This study examines novel geochemical extractions capable of selectively dissolving iron(III) hydroxide oxides, in aqueous solutions of pH 9–11, without damaging fossilised bones or teeth (hydroxidecarbonate‐apatite). This involves the siderophore ligands pyridoxal isonicotinoyl hydrazone (PIH), salicylaldehyde isonicotinoyl hydrazone (SIH), and acetohydroxamic acid (aHA), whose coordination complexes with iron(III) show exceptionally high formation stability constants. The methods have been tested on natural hematite and fossil containing samples from the Riversleigh World Heritage Area in Australia. Both 0.01 mol dm −3 aHA and 0.001 mol dm −3 PIH at pH 9.7 were able to dissolve over 0.1 mmol dm −3 of the goethite coating bone fragments. Abstract : Siderophores have proven capable of selectively dissolving iron(III) hydroxide oxides from the surface of vertebrate fossils without damaging bone material (hydroxidecarbonate‐apatite). Both acetohydroxamic acid (aHA) and pyridoxal isonicotinoyl hydrazone (PIH) at pH 9.7 extracted up to 23 % (mass fraction expressed as percent) of the total iron originally present as goethite‐like solids coating bone fragments, an important advance in efforts to retrieve fossils from difficult matrices.